2015
DOI: 10.1080/19373260.2015.1054957
|View full text |Cite
|
Sign up to set email alerts
|

Exact solution for free vibration of elastically restrained cantilever non-uniform beams joined by a mass-spring system at the free end

Abstract: This article focuses on the free vibration analysis of a non-uniform cantilever beam with an attached mass-spring system at the free end. One end of the beam is elastically restrained against rotation and translation. The height of the beam is assumed constant but the width of the beam exponentially varies. The governing differential equations of the beam, which is a partial differential equation with variable coefficients, and that of the mass-spring system, which is an ordinary differential equation, are fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Firstly, the Euler-Bernoulli beam theory and the extended Hamilton's principle are adopted to obtain the equation of motion of the cantilever [2]. Then, the model reduction is conducted by the Galerkin's method along with the mode function given in [34]. After that, the equation similar to Eq.…”
Section: 4mentioning
confidence: 99%
“…Firstly, the Euler-Bernoulli beam theory and the extended Hamilton's principle are adopted to obtain the equation of motion of the cantilever [2]. Then, the model reduction is conducted by the Galerkin's method along with the mode function given in [34]. After that, the equation similar to Eq.…”
Section: 4mentioning
confidence: 99%
“…Chebyshev polynomials are used in [14] for the solution to a beam of exponentially varying width clamped at one end with the other end attached to a translational or torsional spring. Unfortunately, it is not always possible to determine an exact analytical solution or express the solution in terms of these special functions with exception of very specific types of nonuniformities some of which are discussed in [7][8][9][10][11][12][13][14]. This is a major difficulty with obtaining a dynamic solution for spatially varying beams.…”
Section: Introductionmentioning
confidence: 99%
“…For example, [7,8] considered a beam with an exponentially varying width. It is shown that for this type of geometry the spatial ordinary differential equation (ODE), which is used to determine the natural frequencies and mode shapes, reduces to one with constant coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the TB under axial load rests on the arbitrary variable elastic foundation. On the other hand, Hozhabrossadati [22] presented the exact solution for free vibration of the cantilever EBB with exponentially varying width. The mass-spring system is joined to EBB at the free end.…”
Section: Introductionmentioning
confidence: 99%